Unconscious crime : mental absence and criminal responsibility in Victorian London - Eigen, Joel Peter, 1947- (Johns Hopkins University Press, 2003)
"In Unconscious Crime, Joel Peter Eigen explores cases in which defendants did not conform to the Victorian legal system's existing definitions of insanity yet displayed compelling evidence of mental aberration. They were - or claimed to be - "missing," "absent," or "unconscious": lucid, though unaware of their actions." "Based on extensive research in the Old Bailey Sessions Papers (verbatim courtroom narratives taken down in shorthand during a trial and sold on the street the following day), Eigen's book reveals a growing estrangement between law and medicine over the legal concept of the Person as a rational and purposeful actor with a clear understanding of consequences. Although the McNaughtan Rules of 1843 had formalized the criteria for the Victorian insanity plea, defense attorneys in the cases Eigen studies immediately attempted to broaden the definition of insanity to include mental absence. The Old Bailey judges and the physicians who testified as experts, however, were ever wary of these novel challenges to the idea of human agency and responsibility." "Combining the colorful intrigue of courtroom drama and the keen insights of social history, Unconscious Crime depicts Victorian legal and medical cultures confronting a new understanding of human behavior, and provocatively suggests these trials represent the earliest incarnation of double consciousness and multiple personality disorder in the English court system."--Jacket.